An analysis of the comprehension of pictograms used in the globally harmonized systems for hazard classification and labeling of chemical (GHS) and its suitability for Filipinos - Po, Ronald Aaron Uy (2008)
With the impending implementation of the Blobally Harmonized System for hazard Classification and Labeling (GHS), the Philippines must take steps to prepare to adopt and use this system. A key issue in the implementation of standards is comprehensibility. The GHS uses symbols/pictograms and hazard statements that may be unknown to or cause confusion among potential users. Focus is given to the comprehension of symbols. The main factors of interest are the types of symbols and the amount of information accompanying these symbols. Also considered were the effects of demographic variables such as age, gender, relation of chemicals to occupation, position in the company, educational background, attendance in chemistry lectures in school, chemical-related training attended, and interest in labels in everyday life. A symbol comprehensibility test was conducted, with most samples targeted in the Chemical Industry sector to measure comprehensibility and identify gaps in comprehension. Nine symbols used in the GHS were tested with varying amounts of accompanying information. Different levels of management were surveyed. GHS elements were rated as correctly, partially correct, or incorrectly comprehended. There were only a few elements that were rated as "critical confusions", i.e, the interpretation was the opposite of the intention of the GHS.